Characterization of replication and conjugation of plasmid pWTY27 from a widely distributed Streptomyces species - Wang, Tao (BioMed Central, 2012)
BACKGROUND: Streptomyces species are widely distributed in natural habitats, such as soils, lakes, plants and some extreme environments. Replication loci of several Streptomyces theta-type plasmids have been reported, but are not characterized in details. Conjugation loci of some Streptomyces rolling-circle-type plasmids are identified and mechanism of conjugal transferring are described. RESULTS: We report the detection of a widely distributed Streptomyces strain Y27 and its indigenous plasmid pWTY27 from fourteen plants and four soil samples cross China by both culturing and nonculturing methods. The complete nucleotide sequence of pWTY27 consisted of 14,288 bp. A basic locus for plasmid replication comprised repAB genes and an adjacent iteron sequence, to a long inverted-repeat (ca. 105 bp) of which the RepA protein bound specifically in vitro, suggesting that RepA may recognize a second structure (e.g. a long stem-loop) of the iteron DNA. A plasmid containing the locus propagated in linear mode when the telomeres of a linear plasmid were attached, indicating a bi-directional replication mode for pWTY27. As for rolling-circle plasmids, a single traA gene and a clt sequence (covering 16 bp within traA and its adjacent 159 bp) on pWTY27 were required for plasmid transfer. TraA recognized and bound specifically to the two regions of the clt sequence, one containing all the four DC1 of 7 bp (TGACACC) and one DC2 (CCCGCCC) and most of IC1, and another covering two DC2 and part of IC1, suggesting formation of a high-ordered DNA-protein complex. CONCLUSIONS: This work (i) isolates a widespread Streptomyces strain Y27 and sequences its indigenous theta-type plasmid pWTY27; (ii) identifies the replication and conjugation loci of pWTY27 and; (iii) characterizes the binding sequences of the RepA and TraA proteins.